Evaluasi Usability Pada Aplikasi m-KantorPos dengan Menggunakan Metode Usability Testing - Theresia Karina Situmorang; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
m-KantorPos is a mobile application-based service by PT. Pos Indonesia (Persero). This application needs to be evaluated by measuring the level of usability and exploring problems to produce recommendations for application improvements. The method used in this study is usability testing to measure the components of learnability, efficiency and errors. The interview was used to explore the usability issues of the m-KantorPos application. The System Usability Scale (SUS) questionnaire is used to measure component satisfaction. Usability testing and interviews were conducted on 6 new users of the m-KantorPos application selected based on a range of 19-34 years old and 35-54 years old. The questionnaire was filled by 30 respondents of active users of m-KantorPos application. Based on the test results obtained an ease rate of 75.00%, the speed level of 0.04 goals / sec, an error rate of 0.11 and a satisfaction rate of 50.00%-60.00%. There are 9 usability issues such as invisible menus, menu titles that are too long, vague button colors, slow loading times, application interface layout not flexible and non-responsive, less responsive buttons,. From these problems, recommendations for improvement are formulated according to the usability guidelines that are in accordance with the functions, features and content of m-KantorPos applications.